Alcohol, metabolic risk and elevated serum gamma-glutamyl transferase (GGT) in Indigenous Australians - Haren, Matthew T (BioMed Central, 2010)
BACKGROUND: The interaction between overweight/obesity and alcohol intake on liver enzyme concentrations have been demonstrated. No studies have yet examined the interaction between metabolic syndrome or multiple metabolic risk factors and alcohol intake on liver enzymes. The aim of this study was to examine if alcohol consumption modifies the effect of metabolic risk on elevated serum GGT in Indigenous Australians. METHODS: Data were from N = 2609 Indigenous Australians who participated in a health screening program in rural far north Queensland in 1999-2000 (44.5% response rate). The individual and interactive effects of metabolic risk and alcohol drinking on elevated serum GGT concentrations (≥50 U/L) were analyzed using logistic regression. RESULTS: Overall, 26% of the population had GGT≥50 U/L. Elevated GGT was associated with alcohol drinking (moderate drinking: OR 2.3 [95%CI 1.6 - 3.2]; risky drinking: OR 6.0 [4.4 - 8.2]), and with abdominal obesity (OR 3.7 [2.5 - 5.6]), adverse metabolic risk cluster profile (OR 3.4 [2.6 - 4.3]) and metabolic syndrome (OR 2.7 [2.1 - 3.5]) after adjustment for age, sex, ethnicity, smoking, physical activity and BMI. The associations of obesity and metabolic syndrome with elevated GGT were similar across alcohol drinking strata, but the association of an adverse metabolic risk cluster profile with elevated GGT was larger in risky drinkers (OR 4.9 [3.7 - 6.7]) than in moderate drinkers (OR 2.8 [1.6 - 4.9]) and abstainers (OR 1.6 [0.9 - 2.8]). CONCLUSIONS: In this Indigenous population, an adverse metabolic profile conferred three times the risk of elevated GGT in risky drinkers compared with abstainers, independent of sex and ethnicity. Community interventions need to target both determinants of the population's metabolic status and alcohol consumption to reduce the risk of elevated GGT.